Perencangan Sarana Bawa dan Display Pamer untuk Penggemar Hot Wheels Red Line Club - Mohamad Arif Waskito; Rizky Siswanto (Penerbit Itenas, 2024)
This final project research is the process of designing the design of carrying facilities and exhibition displays intended for Hot Wheels Red Line Club fans. This is based on an opportunity because the Hot Wheels Red Line Club has special value for diecast collectors. The Hot Wheels Red Line Club is an achievement for diecast collectors. The focus of this design is that the product is required to be able to carry three types of Hot Wheels Red Line Club to be displayed at an exhibition held by the Swap Meet Bandung community using a design thinking method approach. has a visual approach to Hot Wheels Red Line Club so as to produce a carrying product designed to group Hot Wheels Red Line Club with other diecasts and can also be used for display at exhibitions. It is hoped that the product will be able to answer user needs through an optimized prototype. The novelty of this research is the transportation facility used to carry the Hot Wheels Red Line Club which has exclusive value.